2008
DOI: 10.1177/016934410802600202
|View full text |Cite
|
Sign up to set email alerts
|

Violence against Women: State Responsibilities in International Human Rights Law to Address Harmful ‘Masculinities’

Abstract: Increasingly, norms of masculinity are the focus of international development programmes aimed at eliminating violence against women, as it is recognised that harmful masculinities must be 'de-mystified', subjected to scrutiny and ultimately reconstructed in order for violence against women to be effectively eliminated. To what extent are these developments reflected in, and to what extent can they rely on, international human rights law as imposing an obligation on states to identify and address aspects of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…First of all, in the research studies men’s violence to women is mainly conceptualized as an instrumental strategy of control, or as a means of reinforcing masculine identity (Anderson, 2008; Gadd, 2000; Hearn, 1998; Messerschmidt, 1999). Therefore, when the issue of neutralization is discussed in homicide cases committed in the context of sexual intimacy involving women as victims and men as offender, either because of masculine identity or with the aim of controlling women’s behavior, it is reported that the single most important motive for murder is the inability of the male offender to accept the termination of a relationship.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, in the research studies men’s violence to women is mainly conceptualized as an instrumental strategy of control, or as a means of reinforcing masculine identity (Anderson, 2008; Gadd, 2000; Hearn, 1998; Messerschmidt, 1999). Therefore, when the issue of neutralization is discussed in homicide cases committed in the context of sexual intimacy involving women as victims and men as offender, either because of masculine identity or with the aim of controlling women’s behavior, it is reported that the single most important motive for murder is the inability of the male offender to accept the termination of a relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a considerable scientific literature already exists describing the role of gender inequality and patriarchy in violence (Alonso, 1996;Anderson, 2008;Baker, Gregware, & Cassidy, 1999;Dobash & Dobash, 1979;Haj-Yahia, 2005;Kandiyoti, 1988;Kim & Sung, 2000;Radford, 1992;392 Homicide Studies 18(4) conducted with 34 male and 5 female prisoners who have been found guilty of murder committed in the name of honor and are serving their sentences in 65 visited Turkish prisons. Special permission was obtained from the Turkish Ministry of Justice to access prison files and conduct semi-structured qualitative interviews with prisoners.…”
Section: Introductionmentioning
confidence: 99%
“…Violence, in the context of gender inequality, can better be understood by taking a broader look at the concept of violence itself. Indeed, a considerable scientific literature already exists describing the role of gender inequality and patriarchy in violence (Alonso, 1996;Anderson, 2008;Baker, Gregware, & Cassidy, 1999;Dobash & Dobash, 1979;Haj-Yahia, 2005;Kandiyoti, 1988;Kim & Sung, 2000;Radford, 1992;Hoyek, Sıdawi, & Mrad, 2005;Sliman, 2005;Van Eck, 2003;Yirmibesoglu, 2007). However, as convincingly argued by Kulczycki and Windle (2011), many previous studies have been substantially marred by poor methodological quality and weak generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Inzicht is gegroeid in de verwevenheid van intiem partnergeweld en de genderasymmetrie in het uitoefenen van controle en dwang (Johnson 2006). Er is groeiende aandacht voor het verband tussen de beeldvorming van het vrouwenlichaam die vrouwen, het vrouwelijke en breder gesteld: het gender-non-conforme tot potentieel doelwit van geweld en vernedering maakt (Anderson 2008 Op basis van ruime definities is een scala aan incidenten geïnventariseerd en opgeteld die qua aard en ernst dusdanig sterk verschillen dat ze deels onvergelijkbaar zijn. Dit doet afbreuk aan de kwaliteit van data.…”
Section: Van Privékwestie Naar Maatschappelijk Probleemunclassified